FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK PADA WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN USAHA DAN PEKERJA BEBAS ( STUDI EMPIRIS PADA KPP SEMARANG CANDISARI ) (Students' Journal of Accounting and Banking, 2014)
This study aims to examine the factors that affect the willingness to pay taxes on individual taxpayers who do usahan and work freely.The sample used in this study is a questionnaire data or primary data distributed in KPP Semarang Candi Sari. The analytical tool used is multiple linear regression t test, f test, and test the coefficient of determination.The results of this study showed that testing of the first hypothesis which states that the variable pay taxes Consciousness is not a significant positive effect on the Willingness to Pay Tax, the second hypothesis which states that knowledge and understanding variables positi significant effect on the Willingness to Pay Tax, the third hypothesis which states that the perception variables either a significant negative effect on the willingness to Pay tax, testing the fourth hypothesis which states that the taxpayer attitudes variable is not significant negative effect on the willingness to Pay tax, testing the fifth hypothesis which states that the service quality variables significant positive effect on willingness to Pay tax, testing the hypothesis that the six states variable tax penalties that significant positive effect on willingness to Pay Tax.Keywords: allocation of General Fund, Capital Expenditure, Revenue Region native, regional gross domestic product